Grid turbulence in compressible flow. - Zwart, Philip J. (University of Ottawa (Canada), 1996)
The flow downstream of a grid in a wind tunnel is of considerable interest for two reasons. Theoretically, it represents a good approximation to the idealized concept of homogeneous and isotropic turbulence, and therefore provides a benchmark to evaluate various analytical theories of turbulence. On the practical side, grids and screens are used extensively in the management of turbulence in a variety of applications. Experimental studies of grid turbulence are numerous in incompressible flow but far scarcer in compressible flow. The present study considers the characteristics of grid turbulence over a range of Mach numbers, M, ranging from the essentially incompressible (M = 0.16), through the moderate subsonic ($0.16 M 0.7)$ and high subsonic $(0.7 M 1.0),$ to the supersonic (M = 1.55). The experiments comprise flow visualization, performed with the shadowgraph method, and mean and fluctuating velocity measurements, made with a laser-Doppler velocimeter. Characteristics of the flow near the grid were visualized in a demonstration nozzle using the schlieren technique. In the moderate subsonic regime, flow visualization indicated that the flow near the grid underwent major changes as M increased. The turbulence intensity and decay characteristics were also found to be influenced, which was attributed to the changes in the flow near the grid. In the high subsonic regime, an unsteady quasi-normal shock was present in the test section. This induced relatively large velocity fluctuations and anisotropic turbulence. In the supersonic regime, stationary oblique shocks generated by the grid were present throughout the test section, which interfered with the turbulence and introduced errors in the measurement technique.
Keywords: Engineering, Mechanical.